THE EFFECT OF COMMUNICATION AND WORK DISCIPLINE ON EMPLOYEE PERFORMANCE AT JATISAMPURNA REGIONAL HOSPITAL - Astuti, Nur Indah; Rangkuti, Zulkifli; Nurmansyah (Yayasan Pendidikan Cahaya Budaya Indonesia, 2025)
This study aims to determine how much influence Communication and Discipline have on the Performance of Employees at Jatisampurna Hospital Bekasi. Good Communication and Discipline are predicted to be variables that can continue to improve employee performance. The purpose of the author in conducting this study was to determine and analyze communication, discipline and employee performance and the magnitude of the influence of communication and discipline on the performance of employees at Jatisampurna Hospital Bekasi, both simultaneously and partially. The method used in this study is a method with a descriptive and verification approach. The sample in this study were 36 employees at Jatisampurna Hospital Bekasi. The data in this study are primary data, where the data was obtained from respondents' answers to the questionnaire that the author distributed. The results of the data analysis that the author has done, it was found that there is an influence of communication and discipline on the performance of employees at Jatisampurna Hospital Bekasi. both partially and simultaneously. Employee performance is influenced by communication and discipline variables by 70.5% and the remaining 25.5% is influenced by other factors not examined in this study.